Experimental and numerical study on mechanical properties of aluminum alloy under uniaxial tensile test - O. Daghfas; A. Znaidi; A. Ben Mohamed; R. Nasri (Fracture and Structural Integrity)
The main objective is to model the behavior of 7075 aluminum alloy and built an experimental database to identify the model parameters. The first part of the paper presents an experimental database on 7075 aluminum alloy. Thus, uniaxial tensile tests are carried in three loading directions relative to the rolling direction, knowing that the fatigue of aircraft structures is traditionally managed based on the assumption of uniaxial loads. From experimental database, the mechanical properties are extracted, particularly the various fractures owing to pronounced anisotropy relating to material. In second part, plastic anisotropy is then modeled using the identification strategy which depends on yield criteria, hardening law and evolution law. In third part, a comparison with experimental data shows that behavior model can successfully describe the anisotropy of the Lankford coefficient.